Stage III Esophageal Squamous Cell Carcinoma Patients With Three-Dimensional Conformal or Intensity-Modulated Radiotherapy: A Multicenter Retrospective Study - Qin, Qin; Ge, Xiaolin; Wang, Xin; Wang, Lan; Li, Chen; Chen, Junqiang; Wang, Xiaomin; Zhao, Yidian; Zhang, Wencheng; Wang, Ping; Pang, Qingsong; Zhang, Kaixian; et al. (Frontiers in Oncology, 2020)
Aim: To evaluate long-term outcome and prognostic factors of stage III esophageal cancer after definitive (chemo) radiotherapy using three dimensional conformal radiotherapy (3DCRT) or intensity-modulated radiotherapy (IMRT) techniques. Methods: Patients with T3N1M0/T4N0-1M0 esophageal squamous cell carcinoma (ESCC) treated with definitive (chemo) radiotherapy from 2002 to 2016 in 10 Chinese medical centers were reviewed. Overall survival (OS) and progression-free survival (PFS) rates were calculated. Prognostic factors were analyzed by Log-rank test and multivariate Cox model. Results: Total 1,450 patients were enrolled. With a median follow-up time of 65.9 months, one-, three-, and five-year OS rates were 69.3%, 36.7%, and 27.7%, respectively, and PFS rates were 58.6%, 32.7%, and 27.4%, respectively. Univariable analyses showed that gender, age, lesion location, lesion length, largest tumor diameter, lymph node metastasis, gross tumor volume, EQD2, short-term response, and concurrent chemotherapy were prognostic factors for OS. Multivariable analyses showed that lesion location, T-classification, GTV size, EQD2, and short-term response to RT were independent prognostic factors for OS, and tumor diameter, GTV size, and short-term response were independent prognostic factors for PFS. Conclusions: This study demonstrated that definitive radiotherapy using 3DCRT and IMRT provides promising outcomes for locally advanced ESCC.